(untitled) (Journal of Partial Differential Equations, 2016)
" The following viscoelastic wave equation with a time-varying delay term in internal feedback |u_t|^03c1u_tt-0394u-0394u_tt+222b^t_0g(t-s)0394u(s)ds+03bc_1u_t(x,t)+03bc_2u_t(x,t-03c4(t))=0, is considered in a bounded domain. Under appropriate conditions on 03bc_1, 03bc_2 and on the kernel g, we establish the general decay result for the energy by suitable Lyapunov functionals."